Consolidative chemotherapy after definitive concurrent chemoradiotherapy for esophageal squamous cell carcinoma patients: a population based cohort study - Lin, Chen-Yuan; Lien, Ming-Yu; Chen, Chi-Ching; Fang, Hsin-Yuan; Lin, Yu-Sen; Chen, Chien-Kuang; Chen, Jian-Xun; Lu, Ting-Yu; Huang, Tzu-Min; Hsieh, Te-Chun; Sun, Shung-Shung; Li, Chia-Chin; et al. (BMC gastroenterology, 2022)
Background The role of consolidative chemotherapy (CCT) for locally advanced esophageal squamous cell carcinoma (LA-ESCC) patients treated with definitive concurrent chemoradiotherapy (dCCRT) is unclear. We aimed to compare the overall survival (OS) of those treated with vs without CCT via a population based approach. Methods Eligible LA-ESCC patients diagnosed between 2011 and 2017 were identified via the Taiwan Cancer Registry. We used propensity score (PS) weighting to balance observable potential confounders between groups. The hazard ratio (HR) of death and incidence of esophageal cancer mortality (IECM) were compared between those with vs without CCT. We also evaluated the OS in supplementary analyses via alternative approaches. Results Our primary analysis consisted of 368 patients in whom covariates were well balanced after PS weighting. The HR of death when CCT was compared to without was 0.67 (95% confidence interval 0.52–0.86, P = 0.002). The HR of IECM was 0.66 ( P = 0.04). The HR of OS remained similarly in favor of CCT in supplementary analyses. Conclusions We found that CCT was associated with significantly improved OS for LA-ESCC patients treated with dCCRT. Randomized controlled trials were needed to confirm this finding.